Analisis Implementasi Ekstrakurikuler Keagamaan Berbasis Mutu Akademik Di Madrasah Tsanawiyah Swasta Mu’allimin Al-Washliyah Medan - Hasibuan, Azimahrani; Salminawati, Salminawati; Dahlan, Zaini (Cetta: Jurnal Ilmu Pendidikan, 2024)
Teachers at the Mu'allimin Al-Washliyah Medan Private Tsanawiyah Madrasah continue to strive to develop the thinking of their students to develop the explanations that have been included in the 2013 curriculum development through the National Education Standards Agency (BSNP). This research was motivated by wanting to know about Religious Extracurriculars Based on Academic Quality at MTs Mu'allimin al-Washliyah Medan, its planning, implementation, how to evaluate it and the inhibiting and supporting factors.  This study uses a qualitative method. This research took place at MTs Mu'allimin al-Washliyah Medan. Data collection techniques use interviews, field observations and documentation studies. Data processing and analysis techniques use data reduction, data presentation and drawing conclusions. The result is planning extracurricular activities, namely planning Al-Quran reading activities and Al-Quran memorization activities. The implementation of extracurricular activities is carried out in several methods, namely; a) Example Method, b) Habituation Method, c) Advice Method, d) Motivation Method, e) Persuasion Method and f) Story Method. There are two ways to evaluate the success of extracurricular activities, namely; a) in summative evaluation, and b) in formative evaluation. The inhibiting factors are divided into two, namely inclusively and exclusively. Inclusively they are; 1) lack of optimal special hours for carrying out guidance and coaching service activities, 2) lack of optimal supervisory attention from the general leadership of PW al-Washliyah who go directly to the field face to face. The exclusive inhibiting factor is the lack of optimal facilities and infrastructure provided directly by the Medan Ministry of Religion, the lack of optimal attention from the Medan City Ministry of Religion itself, the supporting factor is the presence of students at MTQ and STQ events.